Guidelines for Sustainable Intensification of Wheat Production in Sudan - Devkota, Krishna; Idris, Amani A. M.; Mohamed Mustfa, Hala; Elamein, Hala Mohamed Mustafa; Devkota Wasti, Mina Kumari; Eltayeb, Salah; Jabow, Maie Kabbashi Alla; Elkhawad, Mohamed; Abdelgadir Elnour, Omer; Abdelrahman Yousif, Lotfie (2025)
Wheat (Triticum aestivum) is a staple crop with significant importance to the national economy and food security in Sudan. As a primary component of the Sudanese diet, wheat-based products— such as bread, porridge, pastries, pasta, cookies, and sweets—provide a substantial portion of daily caloric intake and contribute to the overall nutritional well-being of the population. Although wheat cultivation in the country dates back to ancient times, it was largely confined to the Northern State (17-22° N) until the 1940s, where traditional wheat consumption was prevalent. With limited land and high production costs in the Northern State, increasing demand led to an expansion southward to warmer regions and irrigated schemes in central and eastern areas (13-15° N). Today, major wheat-growing regions include the Nile River Valley, Gezira Scheme, Northern States, Eastern Sudan, Central Sudan, North Kordofan, and other irrigated areas. Due to the country’s arid and semi-arid climate, production depends heavily on irrigation. The area under wheat cultivation varies year-to-year (187,000 to 321,000 hectares, with a 26% coefficient of variation), influenced by changing weather, market demand, and government policies. In 2021, wheat was grown on approximately 260,000 hectares, making it the sixth-largest crop by area, following sorghum, groundnut, sesame, millet, and melon (FAOSTAT, 2023). Productivity has increased modestly, with a growth rate of 353 kg/ha per year and an average yield of 2.3 t/ha (totaling around 600,000 tons). Despite these gains, local production meets only 23% of domestic wheat demand, necessitating substantial imports. In 2021, the country imported 1.96 million tons of wheat at a cost of USD 621 million, placing a significant strain on its limited foreign exchange reserves (FAOSTAT, 2023). Expanding local production and improving yields are essential strategies for reducing dependence on imports and enhancing food security.